Fortifying horn of Africa with the Djibouti code of conduct in combating piracy and armed robbery against ships: myth or reality - Hamid, Abdul Ghafur@Khin Maung Sein; Ahmad, Md. Hassan@Kyaw Hla Win; Ansari, Abdul Haseeb (2014)
obally, the Djibouti Code of Conduct is the second regional agreement in combating piracy and armed robbery against ships in the Western Indian Ocean and the Gulf of Aden after the ReCAAP. Although it has great potential to contribute in suppressing these maritime crimes in the region, it does not fully address the problem due to its non-binding nature, lack of serious cooperation among Participants, narrow definition of maritime crimes, limitations in information sharing system and poor capacity building. Thus, there is an urgent need to evaluate the efficacy of the Djibouti Code of Conduct. Accordingly, the author intents to analyse its shortcomings and proposes viable solutions. In this paper, Participants are suggested to render binding legal effect to the Djibouti Code of Conduct as soon as possible for the effective suppression of increasing maritime violence crimes. It is also proposed to widen the scope of maritime crimes and include maritime terrorism. It is preferable to remove the two ships requirement from the piracy definition and include the phrase “Exclusive Economic Zone of a State Party” into the definition of armed robbery against ships. All Participants are advised to allow the hot pursuit in their territorial waters in arresting or seizing culprits and cooperate with the requesting Participant. All ships passing through the waters in the region are recommended to notify the flag state, the nearest national focal point of a Participant and the information exchange centre when any incident takes place. All information exchange centres and national focal points should also be well equipped with advanced technologies.